Fibrinogen: cardiometabolic risk marker in obese or overweight children and adolescents - Waldeneide F. Azevedo; Anajás S.C. Cantalice; Nathalia C. Gonzaga; Mônica O. da S. Simões; Anna Larissa V. Guimarães; Danielle F. de Carvalho; Carla Campos Muniz Medeiros (Elsevier, 2015)
Objectives: To determine the prevalence of increased serum fibrinogen levels and its association with cardiometabolic risk factors in overweight or obese children and adolescents. Methods: Cross-sectional study with 138 children and adolescents (overweight or obese) followed at a reference outpatient clinic of the public health care network. Fibrinogen concentration was divided into quartiles, and values above or equal to the third quartile were considered high. The association between high fibrinogen values and cardiometabolic risk factors was assessed using Pearson's chi-squared test or Fisher's exact test, as necessary. Logistic regression was used to adjust variables predictive of fibrinogen levels. Analyses were performed using SPSS version 22.0 and SAS software, considering a confidence interval of 95%. Results: Serum fibrinogen levels were elevated in 28.3% of individuals, showing association with the presence of high CRP (p = 0.003, PR: 2.41, 95% CI: 1.30-4.46) and the presence of four or more risk factors (p = 0.042; PR: 1.78, 95% CI: 1.00-3.17). After a logistic regression, only elevated CRP remained associated with altered fibrinogen levels (p = 0.024; PR: 1.32; 95% CI: 1.09-5.25). Conclusions: Increased fibrinogen was prevalent in the study population and was associated with ultrasensitive C-reactive protein and the presence of four or more cardiovascular risk factors; it should be included in the assessment of individuals at risk. Resumo: Objetivos: Verificar a prevalência de níveis séricos elevados de fibrinogênio e sua associação com os fatores de risco cardiometabólicos em crianças e adolescentes com sobrepeso ou obesidade. Métodos: Estudo transversal com 138 crianças e adolescentes (obesos ou com sobrepeso) acompanhados em um ambulatório de referência da rede pública. A concentração do fibrinogênio foi distribuída em quartis, sendo considerada elevada quando os valores eram iguais ou superiores ao terceiro quartil. A associação entre o valor elevado do fibrinogênio com os fatores de risco cardiometabólicos foi verificada através do teste qui-quadrado de Pearson ou teste exato de Fisher, quando necessário. A regressão logística foi utilizada para ajuste das variáveis preditoras do nível do fibrinogênio. As análises foram realizadas no SPSS 22.0 e SAS, considerando-se o intervalo de confiança de 95%. Resultados: Os níveis séricos de fibrinogênio estiveram elevados em 28.3% dos indivíduos, apresentando associação com a PCR elevada (RP: 2.41; IC 95%: 1.30-4.46, p = 0.003) e com a presença de quatro ou mais fatores de risco (RP: 1.78; IC 95%: 1.00-3.17; p = 0.042). Após a regressão logística, apenas o PCR elevado continuou associado ao fibrinogênio alterado (RP: 1.32; IC 95% 1.09-5.25; p = 0.024). Conclusões: O aumento do fibrinogênio foi prevalente na população estudada e esteve associado à proteína C reativa ultrassensível e ao número igual ou superior a quatro de fatores de risco cardiovasculares, devendo ser incluído na avaliação de indivíduos sob risco. Keywords: Fibrinogen, Obesity, Atherosclerosis, Children, Adolescents, Palavras-chave: Fibrinogênio, Obesidade, Aterosclerose, Crianças, Adolescentes